The Performance of Workers by Utilizing Self-Leadership in Health Sector: A Review - Mohammad Jamil Rizwan; Gancar Candra Premananto; Shah Faisal; Nauroz Khan (Universitas Gadjah Mada, 2023)
Introduction/Main Objectives: Leadership within an organization implies that has positive outcomes on work engagement, optimism, trust, commitment, satisfaction, creativity, and innovation. Every person can move the soul of leadership on themselves self which is called self-leadership. Background Problems: Self-leadership is defined as the process of determining oneself to establish the self-direction and self-motivation to perform. Additionally, self-leadership is designed to influence the positive outcomes of individuals. Novelty: The main focus of this paper is to access self-leadership and its possible impacts on workers or health professions in healthcare facilities. Workers in hospital and other healthcare organizations may show different behavior which can affect their performance. Research Methods: The current study is a descriptive qualitative study that explores the prior studies associated with self-leadership, human behavior, human resources, and performance. At first, relevant studies were collected related to self-leadership and the possible impacts of self-leadership. After that, the authors sum up the relevant studies and discuss the theory of self-leadership and how it can be used in a healthcare organization and hospital. The next step is revealing the author's views regarding the consequences of self-leadership in hospital and healthcare organizations. Finding/Results: As a result, self-leadership is an essential competency for appropriate behavior and improving individual performance.